New Perspectives in Food Allergy - De Martinis, Massimo; Sirufo, Maria Maddalena; Suppa, Mariano; Ginaldi, Lia (International journal of molecular sciences, 2020)
The improvement of the knowledge of the pathophysiological mechanisms underlying the tolerance and sensitization to food antigens has recently led to a radical change in the clinical approach to food allergies. Epidemiological studies show a global increase in the prevalence of food allergy all over the world and manifestations of food allergy appear increasingly frequent also in elderly subjects. Environmental and nutritional changes have partly changed the epidemiology of allergic reactions to foods and new food allergic syndromes have emerged in recent years. The deepening of the study of the intestinal microbiota has highlighted important mechanisms of immunological adaptation of the mucosal immune system to food antigens, leading to a revolution in the concept of immunological tolerance. As a consequence, new prevention models and innovative therapeutic strategies aimed at a personalized approach to the patient affected by food allergy are emerging. This review focuses on these new perspectives and their practical implications in the management of food allergy, providing an updated view of this complex pathology.